Prevalence and factors associated with overweight and obesity among elderly people in a semi-urban area of Chennai - R., Rajkamal; Seralathan, Manikandan; S., Jayakiruthiga (International Journal Of Community Medicine And Public Health, 2018)
Background: Obesity is a medical condition in which excess body fat has accumulated that increases the risk of many adverse health conditions. Obesity being a risk factor facilitates the onset and severity of non-communicable diseases. The objectives of the study were to determine the prevalence of overweight and obesity among elderly people residing in a semi urban area of Chennai and to measure the association between selected factors associated with overweight and obesity among the study population. Methods: A community-based cross-sectional study was carried out in Adayalampet and Nazrathpet, a semi urban area near Chennai, which comes under the field practice area of Department of Community Medicine ACS medical college, Chennai, Tamil Nadu India, during the month of November. Study population included 251 elderly aged 60 years and above. Data were collected by house-to-house survey using pre designed questionnaire and analyzed using SPSS software, version 16.0. Simple proportions were calculated, and chi square test was applied for statistical significance; p value <0.05 was considered as statistically significant. Results: The prevalence of overweight was found to be 30.7% with a 95% CI (24.99-36.41) and obesity was 8.3% (4.89-11.71). Diet, alcohol consumption, physical activity gender, education are associated with overweight/obesity and were statistically significant. Conclusions: The prevalence of overweight and obesity, among elderly people was moderate to high among our study population. Hence concerned efforts through behavior change communication intervention are required to reduce the burden of overweight/obesity among the community.